Correction: Two-Level Scheduling for Video Transmission over Downlink OFDMA Networks. - Mau-Luen Tham; Chee-Onn Chow; Yi-Han Xu; Nordin Ramli (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0148625.].